Pemanfaatan “SAKESI” Sari Kedelai Melancarkan Produksi ASI - Ningrum, Nyna Puspita; Nuraini, Indria; Hubaedah, Annah; Andarwulan, Setiana (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2024)
Background: WHO and UNICEF recommend that newborns receive exclusive breastfeeding for 6 months in early life until the age of two years. The low level of exclusive breastfeeding in the community is caused by various challenges such as the assumption that the supply of breast milk is insufficient and the lack of knowledge about natural methods to increase breast milk production. Community service is carried out in RW II, Siwalankerto, Surabaya. Method: Using a natural approach, educational workshops and direct training in preparing soy milk, aimed at mothers, pregnant women, and posyandu cadres. This program focuses on the use of soy-based products, especially